Identifikasi Diversitas Sumber Pakan Lebah Berbasis Lahan Pekarangan pada Meliponikultur (Identification of Bee Forage Sources Diversity Based on Home Garden in Meliponicultural) - Endah Wahyuningsih; Maiser Syaputra; Pande Komang Suparyan; Andi Tri Lestari (Jurnal Penelitian Hutan Tanaman, 2022)
AbstractKelulut cultivation (meliponiculture) has the potential to be developed in West Nusa Tenggara (NTB) due to the availability of abundant natural bee forage resources. The meliponiculture in NTB is generally still on a home garden-based scale. However, the lack of public knowledge about the variety of plants that produce nectar, pollen, and resin throughout the year is an obstacle to the development of meliponiculture. This study aims to identify the variety of the bee forage and identify constraints and opportunities for developing its cultivation. The results showed that 30 species of plants have the potential as bee forage sources, consisting of seasonal and herbaceous plants. All these plants produce pollen, in which 27 species produce pollen and nectar, and only six can produce all pollen, nectar, and resin. Based on identification results, there are five obstacles and five opportunities in meliponiculture at the research site. The main obstacle was the lack of knowledge about the economic and ecological prospects of meliponiculture. At the same time, the opportunity for cultivation is enormous due to the availability of abundant bee forage resources. Therefore, it is necessary to conduct counseling and training on the economic and ecological prospects of meliponiculture, potential food sources, colony maintenance, and post-harvest processing.Keywords: bee forages, cultivation, home garden, meliponiculture AbstrakBudidaya kelulut (meliponiculture) berpotensi dikembangkan di Nusa Tenggara Barat (NTB) karena ketersediaan sumber daya yang cukup melimpah di alam. Budi daya kelulut di Nusa Tenggara Barat umumnya masih berskala rumah tangga berbasis pekarangan (home garden). Namun kurangnya pengetahuan masyarakat tentang ragam tumbuhan yang menghasilkan nektar, polen, dan/atau resin sepanjang tahun menjadi kendala dalam pengembangan budidayanya. Penelitian ini bertujuan untuk mengidentifikasi jenis tanaman sumber pakan kelulut, mengidentifikasi kendala dan peluang pengembangan budidayanya.  Hasil penelitian menunjukkan terdapat 30 jenis tanaman sumber pakan potensial kelulut yang terdiri dari jenis tanaman tahunan dan tanaman herba. Seluruh tanaman tersebut menghasilkan pollen, 27 jenis diantaranya menghasilkan pollen dan nektar, dan hanya 6 jenis yang dapat menghasilkan pollen, nektar dan resin sekaligus. Hasil identifikasi menunjukkan bahwa ada 5 kendala dan 5 peluang dalam budi daya kelulut di lokasi penelitian. Kendala utama pengembangan budi daya kelulut, yaitu kurangnya pemahaman tentang prospek ekonomi dan ekologi budi daya kelulut, sedangkan peluang budidaya sangat besar karena ketersediaan sumber pakan yang melimpah. Oleh karena itu, perlu dilakukan penyuluhan dan pelatihan tentang prospek ekonomi dan ekologi budi daya kelulut, sumber pakan potensial, pemeliharaan koloni dan pengolahan pasca panen.Kata kunci: budi daya, pekarangan, sumber pakan, kelulut